THE EFFECT OF STORE ENVIRONMENT AND BRAND IMAGE ON CONSUMER BUYING DECISION AT THE BODY SHOP MANADO - Korompis, Faleria Indry (Sam Ratulangi University, 2015)
ABSTRACT Many retailers acknowledge the importance of store environment and brand image to attract the customer interest. The purpose of this research is to analyze the simultaneous and partial effect of Store Environment and Brand Images on Consumer Buying Decision. The populations of this research are people who use The Body Shop Product with 100 respondents. This research uses quantitative analyze by questionnaires and the Multiple Regression Analysis. The result is most of respondents agreed that the indicators related to store environment and brand image, becoming one of their consideration in deciding whether they will make a purchase or not. The Body Shop should pay more attention to the Store Environment and the Brand Image to make the consumer will still be interested buying their product. Keywords : STore environment, Brand Image, Consumer Buying Decision